Evaluation of zinc-doped mesoporous hydroxyapatite microspheres for the construction of a novel biomimetic scaffold optimized for bone augmentation - Yu W (Dove Medical Press, 2017)
Weilin Yu,1,* Tuan-Wei Sun,2,3,* Chao Qi,2,3 Zhenyu Ding,1 Huakun Zhao,1 Shichang Zhao,1 Zhongmin Shi,1 Ying-Jie Zhu,2,3 Daoyun Chen,1 Yaohua He1,4 1Department of Orthopedics, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, 2State Key Laboratory of High Performance Ceramics and Superfine Microstructure, Shanghai Institute of Ceramics, Chinese Academy of Sciences, Shanghai, 3University of Chinese Academy of Sciences, Beijing, 4School of Biomedical Engineering, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai, China *These authors contributed equally to this work Abstract: Biomaterials with high osteogenic activity are desirable for sufficient healing of bone defects resulting from trauma, tumor, infection, and congenital abnormalities. Synthetic materials mimicking the structure and composition of human trabecular bone are of considerable potential in bone augmentation. In the present study, a zinc (Zn)-doped mesoporous hydroxyapatite microspheres (Zn-MHMs)/collagen scaffold (Zn-MHMs/Coll) was developed through a lyophilization fabrication process and designed to mimic the trabecular bone. The Zn-MHMs were synthesized through a microwave-hydrothermal method by using creatine phosphate as an organic phosphorus source. Zn-MHMs that consist of hydroxyapatite nanosheets showed relatively uniform spherical morphology, mesoporous hollow structure, high specific surface area, and homogeneous Zn distribution. They were additionally investigated as a drug nanocarrier, which was efficient in drug delivery and presented a pH-responsive drug release behavior. Furthermore, they were incorporated into the collagen matrix to construct a biomimetic scaffold optimized for bone tissue regeneration. The Zn-MHMs/Coll scaffolds showed an interconnected pore structure in the range of 100–300 µm and a sustained release of Zn ions. More importantly, the Zn-MHMs/Coll scaffolds could enhance the osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells. Finally, the bone defect repair results of critical-sized femoral condyle defect rat model demonstrated that the Zn-MHMs/Coll scaffolds could enhance bone regeneration compared with the Coll or MHMs/Coll scaffolds. The results suggest that the biomimetic Zn-MHMs/Coll scaffolds may be of enormous potential in bone repair and regeneration. Keywords: drug delivery, mesoporous hydroxyapatite microspheres, zinc, biomimicry, scaffold, bone regeneration